Diversity of aquatic hyphomycetes in streambed sediments of temporary streamlets of Southwest India. (April 2015) - Ghate, Sudeep D.; Sridhar, Kandikere R.
Abstract: Assemblages of aquatic hyphomycetes in streambed sediments of nine temporary streamlets in Southwest India were monitored during the wet and dry seasons. Sediments were baited with sterile banyan ( Ficus benghalensis ) leaf disks followed by conidial induction in bubble chambers. Species richness as well as conidial output were higher during the wet than dry season, while it was opposite for diversity. Anguillospora longissima, Cylindrocarpon sp. and Flagellospora curvula were common among the top five spore producers in both seasons. During the wet season, species richness was higher in sandy clay loam sediments than in loam and sandy loam sediments, while species similarity showed a decreasing trend from loam > sandy clay loam > sandy loam sediments. This corresponds to greater dispersal ability of filiform conidia than branched conidia in sediments. The conidial output positively correlated with organic carbon in sediments during the wet season. Highlights: Aquatic hyphomycetes of temporary stream sediments in wet and dry seasons were assessed. Species richness and conidial output were higher during the wet than dry season. Species richness showed decreasing trend from sandy clay loam > loam > sandy loam. Conidial output positively correlated with sediment organic carbon during wet season. Aquatic hyphomycetes survive in sediments during dry season and revive in wet season.